Creation of Ship Navigation Data Using Simulation Technology in Training Module - Mat Radzi, Zulkifly Bin; Jut Weng, Tang; Md Eusoff, Md Hafize; Isnan, Sarah; Aziz, Adenen (Transactions on Maritime Science, 2021)
All ships need navigation data to ensure they stay on track during course-changing maneuvers. Navigation data are usually obtained by shipyards while conducting turning trials at sea. The aim of this research was to generate navigation data for warships, such as the Leander Class Frigate (LCF). The research was conducted using the Ship Bridge Simulator (SBS) simulation technology at the Maritime Centre of the National Defence University of Malaysia (NDUM). Turning trials were conducted at various speeds, rudder angels, and heading changes. Distance to new course, advance and transfer have been tabulated for LCF navigation data. Navigation experts validated the data by nautical chart plotting. The data were found to be highly reliable for the training module. The research was successfully conducted and generated LCF navigation data. The navigation data collected are highly accurate and effective for the naval cadet navigation training module at the NDUM. The SBS software is highly suitable for turning trials and navigation data generation.